THE EFFECTIVENESS OF DEVELOPMENT OF SCIENCE TEACHING MATERIALS WITH VISION OF SCIENCE, ENVIRONMENT, TECHNOLOGY AND SOCIETY (SETS) IN THE NATURAL RESOURCE COMPETENCY CLASS IV OF ELEMENTARY SCHOOL - UMMU JAUHARIN FARDA (JISAE: Journal of Indonesian Student Assessment and Evaluation, 2017)
The aim of this study was to develop science teaching material that feature Science, Environment, Technology, and Society (SETS) vision which covers some criteria namely effective. The study employed Research and Development (R&D) design. The R&D four steps were simplified in to three steps, those were define, design, and develop. The subject of this study was fourth grade Elementary School of SDN Kalibanteng Kidul 03. The techniques of data collections were interview, test, observation, and questionnaire. In analyzing data, the study used descriptive qualitative and quantitative. The result of the developed printed material was effective: 1). The result of study, 2). Increasing the result of study 3). Teacher’s activity, 4). and Student’s activity. Based on the result of this study the learning material has reflected the SETS vision and approach. As such, the science teaching material developed has been justified as effective. Therefore it can be used for extended study to produce a much better product as the supplement for learning science in the competency of natural resources.